Effects of Supplementary Irrigation with Harvested Rainwater on Growth and Leaf Water Use Efficiency of Glycyrrhiza uralensis Seedling - Liu, Xinghong; Liu, Wei; Zhang, Wentai; Hu, Guiqing (Water (Basel), 2024)
Glycyrrhiza uralensis is an important plant in desert ecology, where low rainfall and water scarcity limit its growth. In order to explore harvested rainwater and use for Glycyrrhiza uralensis growth and to reduce water scarcity in Northwest China’s arid area, this study was conducted in April and July of 2023. Five types of slope micro rainwater collection measures, including horizontal terraces, square ridges, and contour ridges, were utilized to monitor rainfall and runoff. Glycyrrhiza uralensis seedlings were utilized as test subjects for supplementary irrigation in pots utilizing the natural drought method. The results show that supplemental irrigation boosts Glycyrrhiza uralensis root growth and water uptake capacity in short-term drought conditions. Irrigation with 42.97 mm enhanced Glycyrrhiza uralensis root length, belowground dry weight, and water use efficiency by 104.5%, 39.54%, and 4.18%. Supplemental irrigation under prolonged drought stress shifted Glycyrrhiza uralensis development from below- to aboveground, resulting in decreased activity of osmotic adjustment material activity in leaves. After 31 days of continuous drought following supplemental irrigation, plant height and aboveground fresh weight increased by 58.16% and 20.03%, respectively, whereas the superoxide dismutase activity was reduced by 63.16% in the 42.97 mm irrigated treatment. Furthermore, under short-term drought stress following supplemental irrigation, leaf water use efficiency was primarily influenced by osmoregulatory substances and plant growth characteristics. Under long-term drought stress, it was influenced by osmoregulatory substances and photosynthetic properties. This research is critical for preventing soil erosion and restoring grassland ecological health in the Ili River Valley.